2007
DOI: 10.1375/twin.10.2.379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Motor Development Between Twins and Singletons in Japan: A Population-Based Study

Abstract: This study was performed using population-based data to analyze whether motor development in early life is different between singletons and twins in Japan. For better comparison and investigation, we divided the 2 groups into a group with a birthweight of 2.5 kg or greater (subgroup A) and a group with a birthweight of less than 2.5 kg (subgroup B), respectively. We analyzed the database of medical check-ups for children aged 3 years between April 2001 and July 2004. They received medical checkups at 4 months,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…Although there was considerable individual variation, almost all children attained the six milestones at the normal ages. The sequence of attainment of six milestones was different from the WHO study, however, consistent with Chinese folklore (sitting within 6 months, rolling over within 7 months, crawling within 8 months, standing with assistance within 9 months, walking within 12 months) and reflected the findings of Japanese (Yokoyama et al, ) and Vietnamese studies (Kulkarni et al, ). The median month‐age at which children achieved sitting without support, crawling on hands and knees, and standing alone was close to the median age of the WHO standards.…”
Section: Discussionsupporting
confidence: 64%
“…Although there was considerable individual variation, almost all children attained the six milestones at the normal ages. The sequence of attainment of six milestones was different from the WHO study, however, consistent with Chinese folklore (sitting within 6 months, rolling over within 7 months, crawling within 8 months, standing with assistance within 9 months, walking within 12 months) and reflected the findings of Japanese (Yokoyama et al, ) and Vietnamese studies (Kulkarni et al, ). The median month‐age at which children achieved sitting without support, crawling on hands and knees, and standing alone was close to the median age of the WHO standards.…”
Section: Discussionsupporting
confidence: 64%
“…Pediatric health care providers may use these standards to flag children at risk for developmental delays or help identify late achievers. Predictors of later attainment of motor milestones include earlier gestational age [2, 3], disease or disability status [46], twin status [79], insufficient dietary and nutrient intake [6, 1012], supine sleep position [1315], a poor home environment [1618], and low socio-economic status [17]. Although the WHO outlined a range of ages for normal attainment of motor milestones, earlier achievement may be associated with some beneficial outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that all motor milestones were attained at slower age by triplets with a birthweight of less than 2 kg compared to twins with a birthweight of less than 2.5 kg, whereas there were no differences in development between triplets with a birthweight of greater than 2 kg and twins with a birthweights of greater than 2.5 kg (Yokoyama et al, 2007). Most notable, the mean age of attaining an ability to walk independently was 14.05 months and 12.98 months in Japanese triplets and Japanese twins, respectively, with differences being almost one month.…”
Section: Discussionmentioning
confidence: 57%
“…After adjusting for gestational age, singletons attained motor development facilitating crawling, walking holding on, and walking independently slower than triplets with a birthweight of less than 2 kg. Our population-based study on comparison of motor development between twins and singletons (Yokoyama et al, 2007) identified that after adjusting for gestational age, singletons with a birthweight of less than 2.5 kg attained motor development facilitating walking independently slower than twins with a birthweight of less than 2.5 kg. This study of twins was consistent with the present results for triplets.…”
Section: Discussionmentioning
confidence: 95%